Knowledge About Dental And Oral Hygiene Using Dental Health Monopoly Media - Putri, Sasqia Aufandra; Isnanto; Sugito, Bambang Hadi (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
Dental and oral hygiene problems are problems commonly experienced by elementary school children. Based on preliminary data at SDN Ganung Kidul 1 Nganjuk, 80% of students have poor knowledge about oral hygiene. This study aims to determine the knowledge of fourth grade students at SDN Ganung Kidul 1 Nganjuk regarding dental and oral hygiene using dental health monopoly media. The method used was descriptive with 28 students as respondents. Data collection instruments used pre-test and post-test questionnaires. The results showed that the level of knowledge of students regarding the meaning, benefits, foods that help clean teeth and mouth, consequences, and how to brush their teeth before playing was in the poor category, with an average of 54.6% and after playing dental health monopoly in the good category, with an average of 86.8%. Dental health monopoly media is used as a tool in the counseling and learning process, which helps convey information about dental hygiene to elementary school students.